Respuesta :

Space

Answer:

x = (y + 26)/5

Step-by-step explanation:

Order of Operations: BPEMDAS

Step 1: Write out equation

y + 6 = 5(x - 4)

Step 2: Distribute

y + 6 = 5x - 20

Step 3: Isolate x

y + 26 = 5x

Step 4: Isolate variable x

(y + 26)/5 = x

Step 5: Rewrite

x = (y + 26)/5

Answer:

y = 5x - 26

Step-by-step explanation:

Since x is the independent variable, you have to solve for y.

y + 6 = 5(x-4)

Now distribute:

y + 6 = 5x - 20

subtract the 6 from both sides

y + 6 - 6 = 5x - 20 - 6

y = 5x - 26